Helicobacter pylori-infected human neutrophils exhibit impaired chemotaxis and a uropod retraction defect - Prichard, Allan; Khuu, Lisa; Whitmore, Laura C.; Irimia, Daniel; Allen, Lee-Ann H. (Frontiers in Immunology, 2022)
Helicobacter pylori is a major human pathogen that colonizes the gastric mucosa and plays a causative role in development of peptic ulcers and gastric cancer. Neutrophils are heavily infected with this organism in vivo and play a prominent role in tissue destruction and disease. Recently, we demonstrated that H. pylori exploits neutrophil plasticity as part of its virulence strategy eliciting N1-like subtype differentiation that is notable for profound nuclear hypersegmentation. We undertook this study to test the hypothesis that hypersegmentation may enhance neutrophil migratory capacity. However, EZ-TAXIScanTM video imaging revealed a previously unappreciated and progressive chemotaxis defect that was apparent prior to hypersegmentation onset. Cell speed and directionality were significantly impaired to fMLF as well as C5a and IL-8. Infected cells oriented normally in chemotactic gradients, but speed and direction were impaired because of a uropod retraction defect that led to cell elongation, nuclear lobe trapping in the contracted rear and progressive narrowing of the leading edge. In contrast, chemotactic receptor abundance, adhesion, phagocytosis and other aspects of cell function were unchanged. At the molecular level, H. pylori phenocopied the effects of Blebbistatin as indicated by aberrant accumulation of F-actin and actin spikes at the uropod together with enhanced ROCKII-mediated phosphorylation of myosin IIA regulatory light chains at S19. At the same time, RhoA and ROCKII disappeared from the cell rear and accumulated at the leading edge whereas myosin IIA was enriched at both cell poles. These data suggest that H. pylori inhibits the dynamic changes in myosin IIA contractility and front-to-back polarity that are essential for chemotaxis. Taken together, our data advance understanding of PMN plasticity and H. pylori pathogenesis.